PENGARUH EFIKASI DIRI DAN FASILITAS BELAJAR TERHADAPPRESTASI BELAJAR SISWA PROGRAM KEAHLIAN PEMASARAN SMK NEGERI 1 SUKOHARJO TAHUN AJARAN 2015/2016 - Rofiqi Haris; Dewi Kusuma Wardani; Jonet Ariyanto Nugroho (Department of Economics Education, Universitas Sebelas Maret, 2017)
The objective of the research is to understand: (1) the influence of self efficacy and learning facilities on the students’ achievement in the marketing department of SMK Negeri 1 Sukoharjo academic year of 2015/2016, (2) the influence of self efficacy on the students’ achievement in the marketing department of SMK Negeri 1 Sukoharjo academic year of 2015/2016, (3) the influence of learning facilities on the students’ achievement in the marketing department of SMK Negeri 1 Sukoharjo academic year of 2015/2016.This research was a causal associative research with quantitative approach. Population and sample of the research were students in class X and XI in the marketing department of SMK Negeri 1 Sukoharjo. The samples were chosen through proportional random sampling. Data were collected by means of questionnaire. Try Out was carried out within activities outside of the samples from class X and XI Marketing. Validity result of the questionnaire were valid with high reliability value. Technique of analyzing data used was multiple regression, t test and f test.Based on the research findings, it can be concluded that (1) there was some influence of self efficacy and learning facilities on the students’ achievement in the marketing department of SMK Negeri 1 Sukoharjo. This was shown by the value of fcalculated > ftable (12.111 > 3.070), (2) there was some influence of self efficacy on the students’ achievement in the marketing department of SMK Negeri 1 Sukoharjo. This was shown by the value of tcalculated > ttable (1.927 > 1.657) (3) there was some influence of learning facilities on the students’ achievement in the marketing department of SMK Negeri 1 Sukoharjo. This was shown by the value of tcalculated > ttable (4.129 > 1.657).